2018
DOI: 10.1080/09571736.2018.1448430
|View full text |Cite
|
Sign up to set email alerts
|

Mother tongue plus two languages: are Scottish primary teachers confident to deliver?

Abstract: Recent policy reforms in Scotland mean that all primary teachers are expected to teach a foreign language (FL) to children from age 5, introducing a second language around age 9. This small-scale research study aimed to ascertain 38 primary teachers' perceptions of their confidence to teach a FL to primary learners and what they felt would be helpful in developing their language proficiency and language teaching pedagogy. The teachers, while enthusiastic about the thinking behind the policy, expressed concern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…They appeared to have an awareness of theory and illustrated its application, without actually mentioning it. Students' lack of explicit theoretical referencing when reflecting echoes findings in previous work (Valdera and Crichton, 2018) which found that students, although clearly conscious of the theory underpinning their planning and evaluations of lessons, did not articulate it unless prompted. This raises the question of whether it is more important that student teachers can identify theories and label actions taken accordingly, or use the theory that they have studied implicitly to plan and deliver effective lessons, where constructivist principles, for example, are evident.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…They appeared to have an awareness of theory and illustrated its application, without actually mentioning it. Students' lack of explicit theoretical referencing when reflecting echoes findings in previous work (Valdera and Crichton, 2018) which found that students, although clearly conscious of the theory underpinning their planning and evaluations of lessons, did not articulate it unless prompted. This raises the question of whether it is more important that student teachers can identify theories and label actions taken accordingly, or use the theory that they have studied implicitly to plan and deliver effective lessons, where constructivist principles, for example, are evident.…”
Section: Discussionsupporting
confidence: 59%
“…A secondary aim was to track evaluations of the PSTs' understanding of language and activities for use in primary classrooms, whether they could reflect on their learning to inform understanding of primary learners' foreign language development. While early learning of modern foreign languages (MFLs) is seen as a good thing in Scotland (Education Scotland, 2015), their mandatory inclusion in the primary curriculum since 2012 (Scottish Government, 2012) has caused some stress for primary teachers, most of whom have little foreign language proficiency, nor understanding of effective pedagogy (Valdera Gil and Crichton, 2018), thus the practicalities regarding pronunciation and grammar structures of a foreign language (Myhill et al, 2013) are a pressing concern.…”
Section: Aimsmentioning
confidence: 99%
“…Based on the data, she agrees to teach English based on the curriculum provided. Gil and Crichton (2018) conveyed their study where young learner teachers are highly eager to teach English but are still unsure to practice it because of the grammar and pronunciation challenges. Besides, Fransischa and Syafei's (2016) research showed that the children failed to acquire new pronunciation if they got it from unprofessional sources.…”
Section: Compatible Media Use In Learning Englishmentioning
confidence: 99%
“…Furthermore, although long term funding for Wales' and Scotland's plans remains uncertain, it is of great interest for NI to consider how and why these two small UK nations in particular developed such ambitious policies. Both the Welsh and Scottish policies are strongly aligned with the European goal of 'mother tongue plus competency in two foreign languages' (Valdera-Gil & Crichton, 2018). Scotland, for its part, has a long political tradition of a stronger European orientation than England, recently marked by its decided vote in favour of remaining in the EU.…”
Section: Walesmentioning
confidence: 99%